"I Want to Go Home": Homesickness Experiences and Social-Support-Seeking Practices. (November 2016) - Scharp, Kristina M.; Paxman, Christina G.; Thomas, Lindsey J.
Almost everyone experiences homesickness at some point in their life, regardless of their age. Given the deleterious outcomes associated with homesickness, this study explores what homesick individuals miss about their homes, what their homes mean to them, and how individuals seek support when they are homesick. Thirty-four in-depth interviews were collected, and results from a content analysis indicate that there are 12 distinct content areas that individuals miss about their homes. Results suggest that activities (100%), family (97%), feelings (100%), and places (97%) are the most salient for homesick individuals. Furthermore, a thematic analysis reveals that "home" is generally synonymous with a comfortable and safe environment. Although the majority of participants reported that they did not seek social support when they were homesick, those who sought support did so both directly and indirectly. Practical implications and directions for future research are discussed.